2018
DOI: 10.1038/s41598-018-30295-y
|View full text |Cite
|
Sign up to set email alerts
|

A controlled aquarium system and approach to study the role of sponge-bacteria interactions using Aplysilla rosea and Vibrio natriegens

Abstract: Sponge-bacteria interactions are very important due to their ecological and biological significance. To understand the impact of interactions between sponges and bacteria (both associated with and external to sponges) on sponge-associated microbial diversity, sponge metabolite profiles and bioactivity, we used a controlled aquarium system and designed an experimental approach that allows the study of sponge-bacteria interactions in a well-defined manner. To test the feasibility of this approach, this system wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Originally, V. natriegens was only known to live in salt marsh mud and estuarine environments (Payne, 1958). Gradually, as more research became public, it became clear that V. natriegens is ubiquitous and widespread in most of our oceans, inhabiting various niches within them (Payne, 1958; Benbouzid‐Rollet et al ., 1991; Mehbub et al ., 2018; Kim et al ., 2019; Peng et al ., 2020). Based on its ability to survive in a low metabolic state for extended periods of time when the nutrient pool is depleted (Nazly et al ., 1980) and its capacity to utilize a wide range of substrates to outgrow competitors with its fast replication (Nazly et al ., 1980; Benbouzid‐Rollet et al ., 1991), it is unsurprising that it was found to be an important founding member in marine biofilms (Nivens et al ., 1986).…”
Section: Ecologymentioning
confidence: 99%
See 2 more Smart Citations
“…Originally, V. natriegens was only known to live in salt marsh mud and estuarine environments (Payne, 1958). Gradually, as more research became public, it became clear that V. natriegens is ubiquitous and widespread in most of our oceans, inhabiting various niches within them (Payne, 1958; Benbouzid‐Rollet et al ., 1991; Mehbub et al ., 2018; Kim et al ., 2019; Peng et al ., 2020). Based on its ability to survive in a low metabolic state for extended periods of time when the nutrient pool is depleted (Nazly et al ., 1980) and its capacity to utilize a wide range of substrates to outgrow competitors with its fast replication (Nazly et al ., 1980; Benbouzid‐Rollet et al ., 1991), it is unsurprising that it was found to be an important founding member in marine biofilms (Nivens et al ., 1986).…”
Section: Ecologymentioning
confidence: 99%
“…While direct evidence for such growth‐promoting interactions between V. natriegens and plants has yet to be identified, several interactions with marine animals are well‐described. For instance, it was shown that the sponge Aplysilla rosea develops a more diverse microbiome when exposed to V. natriegens (Mehbub et al ., 2018). This might help to protect the sponge from colonization by pathogenic microbes via niche exclusion.…”
Section: Ecologymentioning
confidence: 99%
See 1 more Smart Citation